CTBP1 and metabolic syndrome induce an mRNA and miRNA expression profile critical for breast cancer progression and metastasis - Farré, Paula Lucía (2018)
Metastatic breast cancer (BrCa) is still one of the main causes of cancer death in women. Metabolic syndrome (MeS), a risk factor for BrCa, is associated to high grade tumors, increased metastasis and recurrence of this disease. C-terminal binding protein 1 (CTBP1) is a co-repressor of tumor suppressor genes that is activated by low NAD+/NADH ratio. Previously, we demonstrated that CTBP1 hyperactivation by MeS increased tumor growth in MDA-MB-231-derived xenografts regulating several genes and miRNAs. In this work, our aim was to elucidate the role of CTBP1 and MeS in BrCa metastasis. We found that CTBP1 protein diminished adhesion while increased migration of triple negative BrCa cells. CTBP1 and MeS modulated the expression of multiple genes (ITGB4, ITGB6, PRSS2, COL17A1 and FABP4) and miRNAs (miR-378a-3p, miR-146a-5p, let-7e-3p, miR-381-5p, miR-194-5p, miR-494- 3p) involved in BrCa progression of MDA-MB-231-derived xenografts. Furthermore, we demonstrated that MeS increased lung micrometastasis and liver neoplastic disease in mice. CTBP1 hyperactivation seems to be critical for MeS effect on BrCa metastasis since CTBP1 depletion completely impaired the detection of circulating tumor cells. Our results highlight CTBP1 and MeS impact on BrCa progression positioning them as key properties to be considered for BrCa patient prognosis and management.